The Moving Home Effect: A Quasi Experiment Assessing Effect of Home Location on the Offence Location - Wheeler, Andrew (Journal of quantitative criminology, 2012)
Objectives This study aims to test whether the home location has a causal effect on the crime location. To accomplish this the study capitalizes on the natural experiment that occurs when offender’s move, and uses a unique metric, the distance between sequential offenses, to determine if when an offender moves the offense location changes. Methods Using a sample of over 40,000 custodial arrests from Syracuse, NY between 2003 and 2008, this quasi-experimental design uses t test’s of mean differences, and fixed effects regression modeling to determine if moving has a significant effect on the distance between sequential offenses. Results This study finds that when offenders move they tend to commit crimes in locations farther away from past offences than would be expected without moving. The effect is rather small though, both in absolute terms (an elasticity coefficient of 0.02), and in relation to the effect of other independent variables (such as the time in between offenses). Conclusions This finding suggests that the home has an impact on where an offender will choose to commit a crime, independent of offence, neighborhood, or offender characteristics. The effect is small though, suggesting other factors may play a larger role in influencing where offenders choose to commit crime.